Effects of comorbid conditions on health-related quality of life in youth with Type 2 diabetes: the TODAY clinical trial. (November 2015) - Larkin, Mary E; Walders-Abramson, Natalie; Hirst, Kathryn; Keady, Joyce; Ievers-Landis, Carolyn E; Venditti, Elizabeth M; Yasuda, Patrice M
Aim: To explore associations between health-related quality of life (HRQOL) and comorbidities in youth with Type 2 diabetes.Patients & methods: Of 699 youth in the TODAY study, 685 (98%) had baseline HRQOL data, 649 (93%) at 6 months and 583 (83%) at 24 months. Comorbidities were defined by sustained abnormal values and treatment regimens.Results: At baseline, 22.2% of participants demonstrated impaired HRQOL. Only depressive symptoms distinguished those with versus without impaired HRQOL and were significantly related to later impaired HRQOL (p < 0.0001). A significant correspondence between impaired HRQOL and number of comorbidities (p = 0.0003) was noted, but was driven by the presence of depressive symptoms.Conclusion: Results emphasize the need for evaluation of depressive symptoms. Other comorbidities did not have a significant impact on HRQOL in this cohort.